Situation Report: Bulgaria, 26 September 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Official Rejection of Albanian Allegations Regarding Soviet Troops in Bulgaria Bulgaria and Articles 53 and 107 of the UN Statute More on the Bulgarian-Yugoslav Dispute Bulgaria and Developments in Czechoslovakia